2010
DOI: 10.1590/s1807-59322010000900002
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-beta-lactamases among imipenem-resistant Pseudomonas aeruginosa in a brazilian university hospital

Abstract: INTRODUCTION:Imipenem‐resistant Pseudomonas aeruginosa resulting from metallo‐β‐lactamases has been reported to be an important cause of nosocomial infection and is a critical therapeutic problem worldwide, especially in the case of bacteremia.OBJECTIVES:To determine the frequency of metallo‐β‐lactamases among imipenem‐resistant Pseudomonas aeruginosa isolates and to compare methods of phenotypic and molecular detection.METHODS:During 2006, 69 imipenem‐resistant Pseudomonas aeruginosa samples were isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
4
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 28 publications
11
79
4
7
Order By: Relevance
“…Our data suggested that, in our hospital, as well as the SPM clone, there is spread of strains producing MBL of the VIM type. Sporadic reports from Brazil have suggested a similar increase in VIMpositive P. aeruginosa isolates (Franco et al, 2010;Sader et al, 2005), but longitudinal studies that support these data have not been done.…”
Section: Discussionmentioning
confidence: 89%
“…Our data suggested that, in our hospital, as well as the SPM clone, there is spread of strains producing MBL of the VIM type. Sporadic reports from Brazil have suggested a similar increase in VIMpositive P. aeruginosa isolates (Franco et al, 2010;Sader et al, 2005), but longitudinal studies that support these data have not been done.…”
Section: Discussionmentioning
confidence: 89%
“…15 Among β-lactamases, imipenem is the chosen antibiotic for fighting against this bacterium, however P. aeruginosa can disintegrate this antibiotic through MBL enzyme. 16 The rate of imipenem-resistant isolates (46.4%) in our study indicated a menace regarding therapy alternatives in our clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The first MBL (IMP1) was detected in Serratiam arcescens in Japan, 1991 (6). Since then, other kinds of MBLs including VIM, SIM, SPM, GIM, AIM were detected around the world (7,8). This type of MBLs naming is based on detection location.…”
Section: Introductionmentioning
confidence: 99%